Percepción social sobre el suicidio en estudiantes de los grados 8° y 9° de una institución Etnoeducativa en Hatonuevo. (2023)
The objective of this research was to analyze the social perception of suicide in students of the 6th and 7th grades of the Ethnoeducational Institution in Hatonuevo la Guajira. The world health organization - WHO and the Pan American Health Organization - PAHO, 2020) defines suicide as a public health problem, considered an important but neglected factor, since in the society in which we live it is stigmatized, it is a myth and a taboo. This is how each case of suicide is a tragedy that seriously affects not only individuals, but also families and communities.,